A New Era in the European Union: Time to Reform the Cyprus National Food Safety System. (December 2013) - Hadjigeorgiou, Andreas
Summary This article critically examines the current National Food Safety System (NFSS) of Cyprus and identifies its main shortcomings related mainly to duplication and overlapping of food safety responsibilities between competent agencies. Although food supply in Cyprus is generally safe, the country does not have a single and independent National Food Safety Authority (NFSA), but a multi‐level, fragmented system divided among several ministries and governmental agencies based on different food inspection tasks. On the contrary, the European Union (EU) and the majority of EU Member States have re‐organised their systems and established stand‐alone authorities at the central or national level. Within this context, the limitations and strengths of a proposed draft law for the establishment of a Cyprus NFSA embedded in the current environment of economic crisis are also discussed. Finally, the findings of a population‐based survey, which was carried out to determine the beliefs and attitudes of interested parties (regular consumers, food business operators and public service directors or head officers) concerning the operation of the NFSS in Cyprus, are presented. The findings are highlighted in relation to the different practices employed in the EU Member States to rebuild their corresponding NFSS.